Culturally adapted evidence-based treatments for adults with substance use problems: A systematic review and meta-analysis. (1st September 2021) - Hai, Audrey Hang; Lee, Christina S.; Abbas, Bilal T.; Bo, Ai; Morgan, Henry; Delva, Jorge
Highlights: Culturally adapted substance use interventions might be efficacious. The overall effect size was 0.23 and statistically significant. We found no treatment moderators. More studies on culturally substance use adapted interventions are needed. Abstract: Background: This systematic review/meta-analysis aimed to synthesize empirical evidence from randomized controlled trials on the efficacy of culturally adapted interventions (CAIs) for substance use and related consequences for adults of color. Methods: Six electronic databases were searched to identify eligible studies. Two reviewers independently screened studies, extracted data, and assessed risks of bias. We used robust variance estimation in meta-regression to synthesize effect size estimates and conduct moderator analyses. Results: Twenty-two studies met the inclusion criteria and were included in the review. The overall effect size was 0.23 (95 % Confidence Interval [CI] = 0.12, 0.35). The subgroup effect sizes for comparing CAIs with inactive controls and with active controls were 0.31 (CI = 0.14, 0.48) and 0.14 (CI=-0.02, 0.29), respectively. The effect sizes for alcohol use, illicit drug use, unspecified substance use outcomes, and substance use related consequences were 0.25 (CI = 0.08, 0.43), 0.35 (CI =-0.30, 1.00), 0.22 (CI=-0.17, 0.62), and 0.02 (CI=-0.11, 0.16), respectively. Moderator analysis showed that CAIs' effects might not vary significantly by treatment model, dose, country, follow-up assessment timing, participant age, or gender/sex. Conclusions: Research on substance use interventions that are culturally adapted for people of color is growing, and more high-quality studies are needed to draw definitive conclusions about CAIs' treatment effects. Our study found CAIs to be a promising approach for reducing substance use and related consequences. We call for more efficacy/effectiveness and implementation research to further advance the development and testing of evidence-based CAIs that meet the unique needs and sociocultural preferences of diverse populations.